2010
DOI: 10.1063/1.3504244
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature crystal structure, specific heat, and dielectric properties of lithium tetraborate Li2B4O7

Abstract: Coherent neutron powder diffraction experiments were carried out together with specific heat, dilatometry, and dielectric spectroscopy studies on Li 2 B 4 O 7 enriched with 11 B isotope to 99.3% at low temperatures. Neither traces of phase transformations nor discontinuous changes in physical properties were observed. Negative thermal expansion, anomalous thermal behavior of selected interatomic distances/angles, isotropic displacement parameters on specific sites as well as dielectric constant were discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…16 NTE has been observed via x-ray powder diffraction 17 and coherent neutron powder diffraction experiments in Li 2 B 4 O 7 . 18,19 The expansion in this material is anisotropic, with the contraction of one lattice parameter dominating the low-temperature volume dependence. The Li ions show strong T dependence of their meansquared displacements around 100 K, temperature at which NTE vanishes in the material.…”
Section: Introductionmentioning
confidence: 99%
“…16 NTE has been observed via x-ray powder diffraction 17 and coherent neutron powder diffraction experiments in Li 2 B 4 O 7 . 18,19 The expansion in this material is anisotropic, with the contraction of one lattice parameter dominating the low-temperature volume dependence. The Li ions show strong T dependence of their meansquared displacements around 100 K, temperature at which NTE vanishes in the material.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal invariability of rigid groups has been proven by single crystal HTXRD and LTXRD studies (HT, high temperature; LT low temperature) of about a dozen of borates [46][47][48][49][50][51][52][53][54][55][56][57][58], etc. These results have been summarized in [26,34,42,43] and are briefly described here.…”
Section: Thermal Invariability Of Rigid B-o Groupsmentioning
confidence: 99%
“…Pioneering works by Wojciechowski et al showed negative compressibility in thin layers of microscopic systems, while Chen et al in the early 1980s result in polymeric NTE materials. In its short span of history, NTE solids have been developed from all classes of materials . Greater flexibility for application can be found in the case of adjustable CTEs by means of connected triangular blocks , multilayed system and sharp particle (needle‐like) reinforced composites .…”
Section: Motivationmentioning
confidence: 99%